(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
Integrating automation and artificial intelligence (AI) into human resource practices will improve business through automation in human resource management. The rapid development of the digital economy in the last 10 years, especially the development of artificial intelligence in the context of new digital and transformational technological skills, has become a new trend in human resource management. The use of CRM systems or other digital platforms in the HR system significantly facilitates processes such as recruitment and selection of personnel, setting KPIs for employees, as well as the reward system. In addition, with the help of digital technologies it is possible to increase labor productivity by 3-4 times. But the digital technologies used today will not give us the opportunity to increase the productivity of the company’s HR department even by 30%. There are a number of reasons for this, and in this article we are going to study the advantages and disadvantages of digital technologies and CRM systems. And also, the advantage of artificial intelligence compared to other digital technologies.